Pobre pai : a construção da identidade em homens pais pobres urbanos - Rubens Ferreira do Nascimento (2000)
This dissertation elucidates a psychosocial concept of identity articulating basic contributions of psychoanalysis with theories of ideology. Based on the fundamental thesis that identity is psychosocial and socioculturally constructed, it is sought to affirm that power relations, in terms of class, gender and race, are significant factors in the construction of masculinity and paternity in the urban working classes. Qualitative research is developed using the case study method. It has as unit: five heterosexual adult men, poor and who are parents in the Metropolitan Region of Belo Horizonte. For data collection, individual and semi-open interviews were used. The thesis is that some poor men seek to identify themselves with the socially valued traits of masculinity; work is one of them, the family is another. In a declining patriarchal context, these poor men, even distanced from the ideological models of masculinity, still find in their father's place a reference of power at the points where they identify themselves as workers and providers. In the place of father, the poor man, who is distanced from the normative or ideological model of universal man, finds a reference of power. It is concluded that men who are not providers or insufficient providers experience themselves diminished in their masculine condition and resort to palliative resources for their narcissistic dissatisfaction. Marital and domestic violence, alcoholism, infidelity, detachment and abandonment of families are seen, in part, as reactions of the male parents to the losses of social place and to the inability or impossibility of the conquest of socially valued positions.